Staphylococcus aureus Infection Influences the Function of Intestinal Cells by Altering the Lipid Raft-Dependent Sorting of Sucrase–Isomaltase - Mergani, AhmedElmontaser; Wanes, Dalanda; Schecker, Natalie; Branitzki-Heinemann, Katja; Naim, Hassan Y.; von Köckritz-Blickwede, Maren (Frontiers in Cell and Developmental Biology, 2021)
Staphylococcus aureus is an important nosocomial and community-acquired facultative intracellular pathogen. Many studies have reported that S. aureus infections are associated with intestinal symptoms, but little is known about the molecular mechanisms implicated in S. aureus-induced alterations of intestinal functions. In this study, we investigated the implication of lipid rafts in the interaction of S. aureus with Caco-2 cells. To assess potential alterations in the lipid raft structure and effects on the hydrolytic function, we utilized sucrase–isomaltase (SI) as the major intestinal α-glucosidase that is associated with and sorted to the apical membrane via lipid rafts. Seven days post-confluent, Caco-2 cells were infected with S. aureus Newman and further incubated for an additional 2 days. After 48 h, the levels of SI expression as well as the enzymatic function of this protein were assessed in the infected versus non-infected cells. Analysis of the sorting behavior of SI to the apical membrane constituted another crucial aspect in studying the effects of S. aureus on Caco-2 cells. For this purpose, the apical membranes or brush border membranes (BBMs; referred to as P2 fraction) were separated in both infected and non-infected cells from the basolateral and intracellular membranes (referred to as P1 fraction) by employing a cationic-based procedure using CaCl2. The data show that there is no significant change in the overall expression levels of SI in the infected versus non-infected cells as assessed by Western blotting analysis using monoclonal anti-SI antibodies. By contrast, a significant decrease in the localization as well as the specific hydrolytic activities of SI toward sucrose and isomaltose (Palatinose) was observed in the BBM (P2 fraction) in Caco-2 cells 48 h post-infection. Concomitantly, the specific SI activities increased in the basolateral membrane/intracellular fraction (P1). Noteworthy, the specific activity of SI in the BBM of infected cells was markedly reduced as compared with that of the non-infected counterparts. The data accumulated from this study strongly suggest that infections with S. aureus influence the final step in the lipid raft-associated trafficking of human SI and thereby may trigger secondary functional gastrointestinal disorders.